Dimensi Spiritual Pimpinan Lembaga Pendidikan Islam - Geri Gunawan, Muhamad; Irawan, Irawan; Mulyana Sapdi, Rohmat (Universitas Pakuan, 2025)
SPIRITUAL DIMENSION OF THE LEADERSHIP OF ISLAMIC EDUCATIONAL INSTITUTIONSThis study explores the dimensions of spiritual leadership at STIT Al-Ihsan based on the perspectives of its academic community. The research aims to analyze how spiritual values are embedded in leadership practices within an Islamic higher education institution and how these values influence organizational climate and leadership behavior. A qualitative case study approach supported by descriptive quantitative analysis was employed. Data were collected through a Google Form questionnaire containing Likert-scale items and open-ended questions, and analyzed using content analysis. The findings reveal that spiritual leadership at STIT Al-Ihsan is manifested in four key dimensions. The Tauhid dimension emerged as the strongest, indicating that divine orientation serves as the foundation of decision-making processes and leadership direction. The Akhlak dimension scored high and was reflected through moral integrity, exemplary conduct, and respectful communication. The Amanah dimension showed a moderate tendency, marked by a strong sense of responsibility, although transparency and policy consistency still require reinforcement. The Ukhuwah dimension obtained the lowest tendency among the four, suggesting that collegial relations exist but participatory communication remains limited. Overall, the study highlights that spirituality forms a substantive and strategic basis for leadership within Islamic education institutions.